Refugees, governance, and sustainable environment: PQARDL method - Bildirici, Melike (SPRINGER HEIDELBERG, 2022)
Although many variables that have adverse impacts on the sustainable environment are investigated from many aspects, some variables are missing. In this study, it will be simultaneously focused on the relation between refugees, governance, sustainable environment, economic growth, energy consumption, and supplementary explanatory variables, HDI, the trade deficit, and financial development, for Bangladesh, Ethiopia, Jordan, Lebanon, Pakistan, Sudan, and Uganda using the panel quantile autoregressive distributed lag (PQARDL) and causality methods for the 1996-2019 period. Long-run coefficients found by PQARDL method showed the evidence of the long-run relationship between the sustainable environment, refugee population, governance, economic growth, energy consumption, and explanatory variables. Both traditional and Dumitrescu and Hurlin (2012) causality tests determined the evidence of a unidirectional causality from political and economic governance to greenhouse gas (GHG) emissions and deforestation, as well as a unidirectional causality from refugees to GHG emissions and deforestation.
Keywords: Refugee population; Asylum; Sustainable environment; Deforestation; GHG emissions; HDI; Financial development; PQARDL Granger causality; CARBON-DIOXIDE EMISSIONS; LAGRANGE MULTIPLIER TEST; ECONOMIC-GROWTH; ENERGY-CONSUMPTION; INTERNAL MIGRATION; OUT-MIGRATION; INSTITUTIONAL QUALITY; BIOMASS CONSUMPTION; POLICY FORMATION; CO2 EMISSIONS; Environmental Sciences & Ecology